The Concept of Commercial Legal Entities in Kazakhstan and Foreign Legislation - TOLEUBAI, Azat M.; KIZDARBEKOVA, Antonina S. (Journal of Advanced Research in Law and Economics; Vol 9 No 7 (2018): JARLE Volume IX Issue 7(37) Winter 2018DO - 10.14505//jarle.v9.7(37).31, 2019)
The relevance of the study is due to the fact that in Kazakhstan a list of legal entities is defined by law. At the same time, a different approach is defined for commercial and non-commercial organizations. In this context, this article aims to analyze the main features of commercial legal entities under the legislation of leading foreign countries. Leading approach to the study of this problem is the comparative method that has afforded revealing peculiarities of regulation of legal entities under consideration within Kazakhstan and foreign countries. In the article the suggestions for improving the legislation of Kazakhstan are presented on the basis of foreign experience. The materials of the paper imply the practical significance for the university teachers of the legal specializations.